Names of the Worn-on-the-Shoulder Garments in the Subdialects of Pidhaytsi Region (Linguostylistic Studies, 2017)
In recent decades, colloquial language became the object of study for many linguists. Research of various thematic groups of everyday vocabulary provides important information that extends the empirical base of the Ukrainian dialectology. Research of everyday vocabulary of Pidhaytsi region revealed that Pidhaytsi subdialects are central and primary to the Naddnistriansk dialect and to some extent represent the characteristic features of all the subdialects of Naddnistriansk dialect of south-western local dialectal speech in general.This article analyzes the features of the names of the worn-on-shoulder garments used in Pidhaytsi subdialects. The study offers insights into the semantic peculiarities of each of the identified nominations, its etymology, internal form or word from which it originates, and reveals certain methods and means of naming the shoulder-worn garments in the Naddnistriansk dialect .The article elucidates relation of the researched lexicon to the similar vocabulary of other Ukrainian dialects and the Ukrainian literary language, and highlights the issues of lexical parallels in the Slavic languages.
Keywords: subdialect; seme; lexical item; nomen; lexical-semantic group; names of clothes